Non-resonant optical excitation of mode-locked electron spin coherence in (In,Ga)As/GaAs quantum dot ensemble - Schwan, A.; Varwig, S.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Applied Physics Letters)

Electron-nuclei spin coupling in GaAs—Free versus localized electrons - Huang, J.; Chen, Y. S.; Ludwig, A.; Reuter, Dirk; Wieck, A. D.; Bacher, G. (Applied Physics Letters)

Fabrication and characterization of ambipolar devices on an undoped AlGaAs/GaAs heterostructure - Chen, J. C. H.; Wang, D. Q.; Klochan, O.; Micolich, A. P.; Das Gupta, K.; Sfigakis, F.; Ritchie, D. A.; Reuter, Dirk; Wieck, A. D.; Hamilton, A. R. (Applied Physics Letters)

Carrier localization in ZnO quantum wires - Kröger, Philipp; Ruth, Marcel; Weber, Nils; Meier, Cedrik (Applied Physics Letters)

High power impulse magnetron sputtering discharges: Instabilities and plasma self-organization - Ehiasarian, A. P.; Hecimovic, A.; de los Arcos de Pedro, Maria Teresa; New, R.; Schulz-von der Gathen, V.; Böke, M.; Winter, J. (Applied Physics Letters)

Switching performance of a polymer-stabilized antiferroelectric liquid crystal based on bent-core molecules - Atorf, B.; Hoischen, A.; Ros, M. B.; Gimeno, N.; Tschierske, C.; Dantlgraber, G.; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Electrical fine tuning of liquid crystal lasers - Schmidtke, Jürgen; Jünnemann, Gisela; Keuker-Baumann, Susanne; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

The influence of charged InAs quantum dots on the conductance of a two-dimensional electron gas: Mobility vs. carrier concentration - Marquardt, B.; Beckel, A.; Lorke, A.; Wieck, A. D.; Reuter, Dirk; Geller, M. (Applied Physics Letters)

Mode-filtered electron injection into a waveguide interferometer - Buchholz, Sven S.; Kunze, Ulrich; Reuter, Dirk; Wieck, Andreas D.; Fischer, Saskia F. (Applied Physics Letters)

Optically detected nuclear magnetic resonance in n-GaAs using an on-chip microcoil - Chen, Y. S.; Huang, J.; Reuter, Dirk; Ludwig, A.; Wieck, A. D.; Bacher, G. (Applied Physics Letters)

Room temperature spin relaxation length in spin light-emitting diodes - Soldat, Henning; Li, Mingyuan; Gerhardt, Nils C.; Hofmann, Martin R.; Ludwig, Arne; Ebbing, Astrid; Reuter, Dirk; Wieck, Andreas D.; Stromberg, Frank; Keune, Werner; Wende, Heiko (Applied Physics Letters)

Efficient electro-optic switching in a photonic liquid crystal fiber - Lorenz, Alexander; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Electronic structure of self-assembled InGaAs/GaAs quantum rings studied by capacitance-voltage spectroscopy - Lei, W.; Notthoff, C.; Lorke, A.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Electronic structure of self-assembled InGaAs/GaAs quantum rings studied by capacitance-voltage spectroscopy - Lei, W.; Notthoff, C.; Lorke, A.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Nanostructures in p-GaAs with improved tunability - Csontos, M.; Komijani, Y.; Shorubalko, I.; Ensslin, K.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Full-wave rectification based upon hot-electron thermopower - Wiemann, M.; Wieser, U.; Kunze, U.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

An intentionally positioned (In,Ga)As quantum dot in a micron sized light emitting diode - Mehta, M.; Reuter, Dirk; Wieck, A. D.; Michaelis de Vasconcellos, S.; Zrenner, A.; Meier, C. (Applied Physics Letters)

An intentionally positioned (In,Ga)As quantum dot in a micron sized light emitting diode - Mehta, M.; Reuter, Dirk; Wieck, A. D.; Michaelis de Vasconcellos, S.; Zrenner, Artur; Meier, Cedrik (Applied Physics Letters)
We have integrated individual (In,Ga)As quantum dots (QDs) using site-controlled molecular beam epitaxial growth into the intrinsic region of a p-i-n junction diode. This is achieved using an in situ combination of focused ion beam prepatterning, annealing, and overgrowth, resulting in arrays of individually electrically addressable (In,Ga)As QDs with full control on the lateral position. Using microelectroluminescence spectroscopy we demonstrate that these QDs have the same optical quality as optically pumped Stranski–Krastanov QDs with random nucleation located in proximity to a doped interface. The results suggest that this technique is scalable and highly interesting for different applications in quantum devices.

Nonpolar cubic AlGaN/GaN heterojunction field-effect transistor on Ar+ implanted 3C–SiC (001) - Tschumak, E.; Granzner, R.; Lindner, Jörg; Schwierz, F.; Lischka, K.; Nagasawa, H.; Abe, M.; As, Donald (Applied Physics Letters)
A heterojunction field-effect transistor (HFET) was fabricated of nonpolar cubic AlGaN/GaN grown on Ar+ implanted 3C–SiC (001) by molecular beam epitaxy. The device shows a clear field effect at positive bias voltages with V_th=0.6 V. The HFET output characteristics were calculated using ATLAS simulation program. The electron channel at the cubic AlGaN/GaN interface was detected by room temperature capacitance-voltage measurements.

Measurement of effective electron mass in biaxial tensile strained silicon on insulator - Feste, Sebastian F.; Schäpers, Thomas; Buca, Dan; Zhao, Qing Tai; Knoch, Joachim; Bouhassoune, Mohammed; Schindlmayr, Arno; Mantl, Siegfried (Applied Physics Letters)
We present measurements of the effective electron mass in biaxial tensile strained silicon on insulator (SSOI) material with 1.2 GPa stress and in unstrained SOI. Hall-bar metal oxide semiconductor field effect transistors on 60 nm SSOI and SOI were fabricated and Shubnikov–de Haas oscillations in the temperature range of T=0.4–4 K for magnetic fields of B=0–10 T were measured. The effective electron mass in SSOI and SOI samples was determined as mt=(0.20±0.01)m0. This result is in excellent agreement with first-principles calculations of the effective electron mass in the presence of strain.

Nonlocal Aharonov–Bohm conductance oscillations in an asymmetric quantum ring - Buchholz, S. S.; Fischer, S. F.; Kunze, U.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Nonlocal Aharonov–Bohm conductance oscillations in an asymmetric quantum ring - Buchholz, S. S.; Fischer, S. F.; Kunze, U.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Ellipsoidal InAs quantum dots observed by cross-sectional scanning tunneling microscopy - Blokland, J. H.; Bozkurt, M.; Ulloa, J. M.; Reuter, Dirk; Wieck, A. D.; Koenraad, P. M.; Christianen, P. C. M.; Maan, J. C. (Applied Physics Letters)

Using a two-dimensional electron gas to study nonequilibrium tunneling dynamics and charge storage in self-assembled quantum dots - Marquardt, B.; Geller, M.; Lorke, A.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Probing the band structure of InAs∕GaAs quantum dots by capacitance-voltage and photoluminescence spectroscopy - Lei, W.; Offer, M.; Lorke, A.; Notthoff, C.; Meier, Cedrik; Wibbelhoff, O.; Wieck, A. D. (Applied Physics Letters)

Magnetotransport in Gd-implanted wurtzite GaN∕AlxGa1−xN high electron mobility transistor structures - Lo, F.-Y.; Melnikov, A.; Reuter, Dirk; Cordier, Y.; Wieck, A. D. (Applied Physics Letters)

Coherent spin dynamics in Permalloy-GaAs hybrids at room temperature - Hohage, P. E.; Nannen, J.; Halm, S.; Bacher, G.; Wahle, M.; Fischer, S. F.; Kunze, U.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Electrical detection of photoinduced spins both at room temperature and in remanence - Hövel, S.; Gerhardt, N. C.; Hofmann, M. R.; Lo, F.-Y.; Reuter, Dirk; Wieck, A. D.; Schuster, E.; Keune, W.; Wende, H.; Petracic, O.; Westerholt, K. (Applied Physics Letters)

Room temperature electrical spin injection in remanence - Hövel, S.; Gerhardt, N. C.; Hofmann, M. R.; Lo, F.-Y.; Ludwig, A.; Reuter, Dirk; Wieck, A. D.; Schuster, E.; Wende, H.; Keune, W.; Petracic, O.; Westerholt, K. (Applied Physics Letters)

Submicrometer periodic patterns fixed by photopolymerization of dissipative structures - Hoischen, A.; Benning, S. A.; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Influence of doping on the photorefractive properties of a polymer-dispersed liquid crystal - Redler, Andreas; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Single-photon level ultrafast all-optical switching - Han, Xiao-Feng; Weng, Yu-Xiang; Wang, Rui; Chen, Xi-Hao; Luo, Kai Hong; Wu, Ling-An; Zhao, Jimin (Applied Physics Letters)

Enhanced transmission of periodic, quasiperiodic, and random nanoaperture arrays - Rockstuhl, Carsten; Lederer, Falk; Zentgraf, Thomas; Giessen, Harald (Applied Physics Letters)

Technique for tilting GaAs photonic crystal nanocavities out of plane - Meier, Cedrik; Hennessy, Kevin (Applied Physics Letters)

Magnetic and structural properties of Gd-implanted zinc-blende GaN - Lo, F.-Y.; Melnikov, A.; Reuter, Dirk; Wieck, A. D.; Ney, V.; Kammermeier, T.; Ney, A.; Schörmann, J.; Potthast, S.; As, D. J.; Lischka, K. (Applied Physics Letters)

Focused ion beam implantation induced site-selective growth of InAs quantum dots - Mehta, M.; Reuter, Dirk; Melnikov, A.; Wieck, A. D.; Remhof, A. (Applied Physics Letters)

Crystalline ZnO with an enhanced surface area obtained by nanocasting - Waitz, T.; Tiemann, Michael; Klar, P. J.; Sann, J.; Stehr, J.; Meyer, B. K. (Applied Physics Letters)
The authors report the synthesis of nanoporous ZnO, which exhibits a periodically ordered, uniform pore system with crystalline pore walls. The crystalline structure is investigated by x-ray diffraction, transmission electron microscopy, and selected area electron diffraction. The large specific surface area and the uniformity of the pore system are confirmed by nitrogen physisorption. Raman spectroscopy along with low-temperature photoluminescence measurements confirms the high degree of crystallinity and gives insight into defects participating in the radiative recombination processes. The authors thank Günter Koch for recording the TEM images and Marie-Luise Wolff for valuable help in the laboratory one of the authors (M.T.) thanks Michael Fröba for the continuous support.

Tuning the threshold voltage of organic field-effect transistors by an electret encapsulating layer - Scharnberg, M.; Zaporojtchenko, V.; Adelung, R.; Faupel, F.; Pannemann, C.; Diekmann, T.; Hilleringmann, Ulrich (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Visible resonant modes in GaN-based photonic crystal membrane cavities - Meier, Cedrik; Hennessy, Kevin; Haberer, Elaine D.; Sharma, Rajat; Choi, Yong-Seok; McGroddy, Kelly; Keller, Stacia; DenBaars, Steven P.; Nakamura, Shuji; Hu, Evelyn L. (Applied Physics Letters)

Ballistic rectification in an asymmetric mesoscopic cross junction - Knop, M.; Wieser, U.; Kunze, U.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Fabrication of genuine single-quantum-dot light-emitting diodes - Schmidt, R.; Scholz, U.; Vitzethum, M.; Fix, R.; Metzner, C.; Kailuweit, P.; Reuter, Dirk; Wieck, A.; Hübner, M. C.; Stufler, S.; Zrenner, A.; Malzer, S.; et al. (Applied Physics Letters)

Control of quantum dot excitons by lateral electric fields - Stavarache, V.; Reuter, Dirk; Wieck, A. D.; Schwab, M.; Yakovlev, D. R.; Oulton, R.; Bayer, M. (Applied Physics Letters)

Coherent spin oscillations in bulk GaAs at room temperature - Hohage, P. E.; Bacher, G.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Inverted spin polarization of Heusler alloys for spintronic devices - Thomas, Andy; Meyners, Dirk; Ebke, Daniel; Liu, Ning-Ning; Sacher, Marc; Schmalhorst, Jan; Reiss, Günter; Ebert, Hubert; Hütten, Andreas (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

GaN blue photonic crystal membrane nanocavities - Choi, Y.-S.; Hennessy, K.; Sharma, R.; Haberer, E.; Gao, Y.; DenBaars, S. P.; Nakamura, S.; Hu, E. L.; Meier, Cedrik (Applied Physics Letters)

Screening effects in InAs quantum-dot structures observed by photoluminescence and capacitance-voltage spectra - Lüttjohann, Stephan; Meier, Cedrik; Lorke, Axel; Reuter, Dirk; Wieck, Andreas D. (Applied Physics Letters)

Photonic bands in two-dimensionally patterned multimode GaN waveguides for light extraction - David, A.; Meier, Cedrik; Sharma, R.; Diana, F. S.; DenBaars, S. P.; Hu, E.; Nakamura, S.; Weisbuch, C.; Benisty, H. (Applied Physics Letters)

Vertically oriented GaN-based air-gap distributed Bragg reflector structure fabricated using band-gap-selective photoelectrochemical etching - Sharma, R.; Haberer, E. D.; Meier, Cedrik; Hu, E. L.; Nakamura, S. (Applied Physics Letters)

Properties of nonpolar a-plane InGaN∕GaN multiple quantum wells grown on lateral epitaxially overgrown a-plane GaN - Chakraborty, Arpan; Keller, Stacia; Meier, Cedrik; Haskell, Benjamin A.; Keller, Salka; Waltereit, Patrick; DenBaars, Steven P.; Nakamura, Shuji; Speck, James S.; Mishra, Umesh K. (Applied Physics Letters)

Depletion characteristics of two-dimensional lateral p‐n-junctions - Reuter, Dirk; Werner, C.; Wieck, A. D.; Petrosyan, S. (Applied Physics Letters)

Wave-form sampling using a driven electron ratchet in a two-dimensional electron system - Müller, T.; Würtz, A.; Lorke, A.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Electron spin injection into GaAs from ferromagnetic contacts in remanence - Gerhardt, N. C.; Hövel, S.; Brenner, C.; Hofmann, M. R.; Lo, F.-Y.; Reuter, Dirk; Wieck, A. D.; Schuster, E.; Keune, W.; Westerholt, K. (Applied Physics Letters)

Screening effects in InAs quantum-dot structures observed by photoluminescence and capacitance-voltage spectra - Lüttjohann, Stephan; Meier, Cedrik; Lorke, Axel; Reuter, Dirk; Wieck, Andreas D. (Applied Physics Letters)

Single-hole transistor in p-type GaAs∕AlGaAs heterostructures - Grbić, Boris; Leturcq, Renaud; Ensslin, Klaus; Reuter, Dirk; Wieck, Andreas D. (Applied Physics Letters)

Spatially periodic liquid crystal director field appearing in a photonic crystal template - Matthias, Heinrich; Röder, Thorsten; Wehrspohn, Ralf B.; Kitzerow, Heinz-Siegfried; Matthias, Sven; Picken, Stephen J. (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Tunable defect mode in a three-dimensional photonic crystal - Mertens, G.; Wehrspohn, R. B.; Kitzerow, Heinz-Siegfried; Matthias, S.; Jamois, C.; Gösele, U. (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Photorefractive polymer-dispersed liquid crystal based on a photoconducting polysiloxane - Paelke, Lutz; Kitzerow, Heinz-Siegfried; Strohriegl, Peter (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Gain and carrier losses of (GaIn)(NAs) heterostructures in the 1300–1550 nm range - Schlichenmaier, C.; Thränhardt, A.; Meier, Torsten; Koch, S. W.; Chow, W. W.; Hader, J.; Moloney, J. V. (Applied Physics Letters)
A microscopic model is used to analyze gain and loss properties of (GaIn)(NAs)∕GaAs quantum wells in the 1.3–1.55μm range, including Auger and radiative recombination. The calculations show that, as long as good material quality can be achieved, growing highly compressively strained samples is preferable due to their specific band structure properties. Optimum laser operation is possible slightly above a peak gain of 1000cm−1 ⁠.

Radiotracer measurements as a sensitive tool for the detection of metal penetration in molecular-based organic electronics - Scharnberg, M.; Hu, J.; Kanzow, J.; Rätzke, K.; Adelung, R.; Faupel, F.; Pannemann, C.; Hilleringmann, Ulrich; Meyer, S.; Pflaum, J. (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Postannealing of magnetic tunnel junctions with ion-bombardment-modified exchange bias - Höink, V.; Sacher, Marc; Schmalhorst, J.; Reiss, G.; Engel, D.; Junk, D.; Ehresmann, A. (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Free-standing, optically pumped, GaN∕InGaN microdisk lasers fabricated by photoelectrochemical etching - Haberer, E. D.; Sharma, R.; Meier, Cedrik; Stonas, A. R.; Nakamura, S.; DenBaars, S. P.; Hu, E. L. (Applied Physics Letters)

The linearly graded two-dimensional p–n junction - Petrosyan, S.; Yesayan, A.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Magnetotransport in C-doped AlGaAs heterostructures - Grbić, B.; Ellenberger, C.; Ihn, T.; Ensslin, K.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Nonequilibrium gain in optically pumped GaInNAs laser structures - Thränhardt, A.; Becker, S.; Schlichenmaier, C.; Kuznetsova, I.; Meier, Torsten; Koch, S. W.; Hader, J.; Moloney, J. V.; Chow, W. W. (Applied Physics Letters)
A theory is presented which couples a dynamical laser model to a fully microscopic calculation of scattering effects. Calculations for two optically pumped GaInNAs laser structures show how this approach can be used to analyze nonequilibrium and dynamical laser properties over a wide range of system parameters.

Fabrication of high-quality two-dimensional electron gases by overgrowth of focused-ion-beam-doped AlxGa1−xAs - Reuter, D.; Riedesel, C.; Schafmeister, P.; Meier, Cedrik; Wieck, A. D. (Applied Physics Letters)

Magnetism and interface properties of epitaxial Fe films on high-mobility GaAs/Al0.35Ga0.65As(001) two-dimensional electron gas heterostructures - Cuenya, B. Roldan; Doi, M.; Keune, W.; Hoch, S.; Reuter, Dirk; Wieck, A.; Schmitte, T.; Zabel, H. (Applied Physics Letters)

Self-induced transparency in InGaAs quantum-dot waveguides - Schneider, S.; Borri, P.; Langbein, W.; Woggon, U.; Förstner, Jens; Knorr, A.; Sellin, R. L.; Ouyang, D.; Bimberg, D. (Applied Physics Letters)
We report the experimental observation and the theoretical modeling of self-induced-transparency signatures such as nonlinear transmission, pulse retardation and reshaping, for subpicosecond pulse propagation in a 2-mm-long InGaAs quantum-dot ridge waveguide in resonance with the excitonic ground-state transition at 10 K. The measurements were obtained by using a cross-correlation frequency-resolved optical gating technique which allows us to retrieve the field amplitude of the propagating pulses.
Keywords: tet_topic_qd

Two- and three-dimensional photonic crystals made of macroporous silicon and liquid crystals - Mertens, Guido; Röder, Thorsten; Matthias, Heinrich; Marsmann, Heinrich; Kitzerow, Heinz-Siegfried; Schweizer, Stefan L.; Jamois, Cecile; Wehrspohn, Ralf B.; Neubert, Mary (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Beam steering in waveguide arrays - Pertsch, T.; Zentgraf, Thomas; Peschel, U.; Bräuer, A.; Lederer, F. (Applied Physics Letters)

Control of the confining potential in ballistic constrictions using a persistent charging effect - Fischer, S. F.; Apetrii, G.; Skaberna, S.; Kunze, U.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Fabrication of quantum point contacts by engraving GaAs/AlGaAs heterostructures with a diamond tip - Regul, J.; Keyser, U. F.; Paesler, M.; Hohls, F.; Zeitler, U.; Haug, R. J.; Malavé, A.; Oesterschulze, E.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

A multipurpose torsional magnetometer with optical detection - Schaapman, M. R.; Christianen, P. C. M.; Maan, J. C.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Increased thermal budget for selectively doped heterostructures by employing AlAs/GaAs superlattices - Reuter, Dirk; Meier, C.; Álvarez, M. A. Serrano; Wieck, A. D. (Applied Physics Letters)

Influence of iron–silicon interaction on the growth of carbon nanotubes produced by chemical vapor deposition - de los Arcos de Pedro, Maria Teresa; Vonau, F.; Garnier, M. G.; Thommen, V.; Boyen, H.-G.; Oelhafen, P.; Düggelin, M.; Mathis, D.; Guggenheim, R. (Applied Physics Letters)

Shift of the photonic band gap in two photonic crystal/liquid crystal composites - Mertens, Guido; Röder, Thorsten; Schweins, Ralf; Huber, Klaus; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Increased thermal budget for selectively doped heterostructures by employing AlAs/GaAs superlattices - Reuter, Dirk; Meier, Cedrik; Álvarez, M. A. Serrano; Wieck, A. D. (Applied Physics Letters)

Azimuthal surface gliding of a nematic liquid crystal - Vorflusev, V. P.; Kitzerow, Heinz-Siegfried; Chigrinov, V. G. (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Gray‐scale in polymer‐stabilized antiferroelectric liquid crystal displays - Strauss, J.; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Bulk‐induced alignment of nematic liquid crystals by photopolymerization - Jain, Sukhmal C.; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Linear electro‐optic effects in polymer‐dispersed ferroelectric liquid crystals - Kitzerow, Heinz-Siegfried; Molsen, Henning; Heppke, Gerd (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)